2008
DOI: 10.1016/j.rgg.2007.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of experimental data on the diffusion coefficients of Fe, Mn, Mg, and Ca in garnets

Abstract: Experimental data on the diffusion coefficients of Fe, Mn, Mg, and Ca in garnets are generalized. Frequency factors (cm2/s), activation energies (cal/mole), and activation volumes (cm3/mole) are optimized. Based on the compensation law, the dependences of diffusion coefficients on pressure (kbar) and temperature (K) have been derived:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…For diffusion in minerals, numerous workers have shown that the MNR is upheld for many diffusing species in individual minerals, with the first study being that of Hart []. Examples include oxygen diffusion in diopside [ Jaoul and Bejina , ], in perovskite [ Berenov et al ., ], and in a wide variety of minerals [ Zheng and Fu , ], silicon diffusion in silicate minerals [ Bejina and Jaoul , ], Fe, Mn, Mg, and Ca diffusion in garnets [ Korolyuk and Lepezin , ] (where Fe, Mn, and Mg are fit as one diffusing species), argon diffusion in sericites [ Batyrmurzaev , ], Fe/Mg interdiffusion in olivines and garnet [ Jaoul and Sautter , ], and Ar, H, Pb, and Sr diffusion in a wide array of minerals [ Zhao and Zheng , ]. Proton diffusion has been studied the most of all diffusing species, and adherence to the MNR has been reported for perovskites [ Kreuer , ], as well as other crustal and upper mantle minerals discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…For diffusion in minerals, numerous workers have shown that the MNR is upheld for many diffusing species in individual minerals, with the first study being that of Hart []. Examples include oxygen diffusion in diopside [ Jaoul and Bejina , ], in perovskite [ Berenov et al ., ], and in a wide variety of minerals [ Zheng and Fu , ], silicon diffusion in silicate minerals [ Bejina and Jaoul , ], Fe, Mn, Mg, and Ca diffusion in garnets [ Korolyuk and Lepezin , ] (where Fe, Mn, and Mg are fit as one diffusing species), argon diffusion in sericites [ Batyrmurzaev , ], Fe/Mg interdiffusion in olivines and garnet [ Jaoul and Sautter , ], and Ar, H, Pb, and Sr diffusion in a wide array of minerals [ Zhao and Zheng , ]. Proton diffusion has been studied the most of all diffusing species, and adherence to the MNR has been reported for perovskites [ Kreuer , ], as well as other crustal and upper mantle minerals discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…At a higher temperature (650°C), the process will take 1 × 10 7 , 5 × 10 7 , 1 × 10 9 , and 1.5 × 10 9 years, respectively. However, the actual D c of elements in natural garnet must be higher than these experimental values (Korolyuk and Lepezin 2008). Considering the possible cooling rate and magmatic time scale of the DTG pluton (<10 7 years), the large size of garnet (~10-20 mm), and Ca and Mg zoning, it seems that diffusion had no significant effects on garnet composition.…”
Section: Discussionmentioning
confidence: 87%
“…The timescale of magmatic processes in granite genesis, from melting to crystallization, rarely exceeds 10 5 years (Villaros et al 2009 and references therein). The experiments of Korolyuk and Lepezin (2008) show that the diffusion coefficients (D c ) of Ca, Mg, Fe, and Mn are in the order D Mn >D Fe >D Mg >D Ca . Diffusion coefficients are pressure-independent, but temperature-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation